2005
DOI: 10.4049/jimmunol.174.7.4127
|View full text |Cite
|
Sign up to set email alerts
|

Tumoricidal Potential of Native Blood Dendritic Cells: Direct Tumor Cell Killing and Activation of NK Cell-Mediated Cytotoxicity

Abstract: Dendritic cells (DCs) are characterized by their unique capacity for primary T cell activation, providing the opportunity for DC-based cancer vaccination protocols. Novel findings reveal that besides their role as potent inducers of tumor-specific T cells, human DCs display additional antitumor effects. Most of these data were obtained with monocyte-derived DCs, whereas studies investigating native blood DCs are limited. In the present study, we analyze the tumoricidal capacity of M-DC8+ DCs, which represent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
93
2
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 80 publications
(103 citation statements)
references
References 56 publications
(68 reference statements)
5
93
2
3
Order By: Relevance
“…Interestingly, although others have reported that pDCs are poorly cytotoxic, 52,71 Stary et al 54 demonstrated that bloodderived pDCs kill tumor cells upon TLR-7/8 activation via a TRAIL-dependent mechanism. Palucka's group also recently described a CD2 þ pDC subset found in human blood that kills tumors in vitro in a TRAIL-dependent fashion (KA Palucka, 77 showed that the rat cytotoxic DCs express NKR-P2, an ortholog of mouse and human NKG2D.…”
Section: Killer Dcsmentioning
confidence: 99%
“…Interestingly, although others have reported that pDCs are poorly cytotoxic, 52,71 Stary et al 54 demonstrated that bloodderived pDCs kill tumor cells upon TLR-7/8 activation via a TRAIL-dependent mechanism. Palucka's group also recently described a CD2 þ pDC subset found in human blood that kills tumors in vitro in a TRAIL-dependent fashion (KA Palucka, 77 showed that the rat cytotoxic DCs express NKR-P2, an ortholog of mouse and human NKG2D.…”
Section: Killer Dcsmentioning
confidence: 99%
“…In addition, they are potent inducers of primary antigen-specific T-cell responses in vitro 11 , and show a superior programming of Th1/Th17 cell polarization as compared with classical CD1c þ DCs 14 . Furthermore, slanDCs induce in vitro tumour-specific cytotoxic T cells and strongly promote natural killer (NK) cell proliferation, NK cytotoxic activity and, in cooperation with neutrophils, NK-derived interferon-gamma (IFNg) production [15][16][17] . However, since the identification and functional analysis of human slanDCs in cancer patients has not been explored yet, in this study, we investigated such an issue.…”
mentioning
confidence: 99%
“…In previous studies, we have shown that activated slanDCs produce large amounts of TNF-a, which essentially contributes to their tumor-directed cytotoxicity. 5,7 In addition, we have shown that activated slanDCs are principal producers of IL-12, which favors the differentiation of naive CD4 þ T cells into Th1 cells and is important in NK cell activation. 6,8 Blood samples were obtained from healthy donors with informed consent.…”
mentioning
confidence: 99%
“…The failure to trigger slanDC activation efficiently can be explained by an insufficient expression of 'danger' molecules by AML cells and/or the production of inhibitory molecules. As a consequence, the capacity of slanDCs to mediate tumor-directed cytotoxicity 7 and to activate tumor-reactive NK cells 8 and T cells 6 may be impaired. In addition, we found that two AML cell samples significantly inhibit TNF-a and IL-12 secretion by activated slanDCs.…”
mentioning
confidence: 99%
See 1 more Smart Citation